Women's Experiences with and Preference for Induction of Labor with Oral Misoprostol or Foley Catheter at Term - ten Eikelder, Mieke L.G.; van de Meent, Marieke M.; Mast, Kelly; Rengerink, Katrien Oude; Jozwiak, Marta; de Graaf, Irene M.; Scholtenhuis, Marloes A. G. Holswilder-Olde; Roumen, Frans J. M. E.; Porath, Martina M.; van Loon, Aren J.; van den Akker, Eline S.; Rijnders, Robbert J. P.; Feitsma, A. Hanneke; Adriaanse, Albert H.; Muller, Moira A.; de Leeuw, Jan W.; Visser, Harry; Woiski, Mallory D.; Weerd, Sabina Rombout-de; van Unnik, Gijs A.; Pernet, Paula J. M.; Versendaal, Hans; Mol, Ben W.; Bloemenkamp, Kitty W. M. (American Journal of Perinatology, 2017)
Objective We assessed experience and preferences among term women undergoing induction of labor with oral misoprostol or Foley catheter.Study Design In 18 of the 29 participating hospitals in the PROBAAT-II trial, women were asked to complete a questionnaire within 24 hours after delivery. We adapted a validated questionnaire about expectancy and experience of labor and asked women whether they would prefer the same method again in a future pregnancy.Results The questionnaire was completed by 502 (72%) of 695 eligible women; 273 (54%) had been randomly allocated to oral misoprostol and 229 (46%) to Foley catheter. Experience of the duration of labor, pain during labor, general satisfaction with labor, and feelings of control and fear related to their expectation were comparable between both the groups. In the oral misoprostol group, 6% of the women would prefer the other method if induction is necessary in future pregnancy, versus 12% in the Foley catheter group (risk ratio: 0.70; 95% confidence interval: 0.55–0.90; p = 0.02).Conclusion Women's experiences of labor after induction with oral misoprostol or Foley catheter are comparable. However, women in the Foley catheter group prefer more often to choose a different method for future inductions.
Keywords: induction of labor; oral misoprostol; Foley catheter; patient experience; patient preference